INOVASI SISTEM TELEMONITORING WARGA ISOLASI MANDIRI BERBASIS INTERNET OF THINGS DI WILAYAH GADINGSARI, SANDEN, BANTUL - Banu Santoso; Afin Nur Ikhsan (Universitas PGRI Yogyakarta, 2022)
This community service develops a telemonitoring tool that is used to monitor the condition of the PDP in self-isolation. With this tool, monitoring can be carried out remotely, and the patient's condition can be detected quickly so that the patient is not brought to the hospital too late. This monitoring device is designed to monitor oxygen saturation (blood pressure), heart rate, and patient body temperature, which is used to identify the patient's condition. The manufacturer of this tool uses an IoT (Internet of Things) system, with a MAX 30102 sensor to measure SpOo2 (blood pressure) and heart rate and a DS18B20 sensor to measure the patient's body temperature. By using the ESP32 microcontroller as an IoT (Internet of Things) device, data such as SpO2 (Oxygen Saturation), heart rate, and body temperature as monitoring parameters can be sent to an Android smartphone which is then forwarded to the ThingSpeak server as a server from Health Workers. Keywords: Covid-19; Telemonitoring; Internet of Things; Devotion